30.7k views
4 votes
A function f(x, y) is called homogeneous of degree n if it satisfies the equation f(tx,ty) = t n f(x, y) for all t, where n is a positive integer. Show that if f(x, y) is homogeneous of degree n, then x ∂ f ∂ x +y ∂ f ∂ y = n f(x, y). (Hint: Try differentiating: find ∂ ∂t t=1 of a homogeneous function f in two ways.)

1 Answer

2 votes

Answer:

It is proved that
x(\partial f)/(\partial x)+y(\partial f)/(\partial y)=nf(x,y).

Explanation:

Given function is,


f(tx, ty)=t^nf(x, y) for all t>0 and n is positive integers.

To show,


x(\partial f)/(\partial x)+y(\partial f)/(\partial y)=n f(x, y)

Let, u=tx and v=ty, then,


f(tx, ty)=t^nf(x, y)


\implies f(u, v)=t^n f(x, y)\hfill (1)

differentiate partially with respect to x we get,

[tex}\frac{\partial}{\partial x}f(u,v)=\frac{\partial}{\partial x}(t^nf(x, y))[/tex]


\implies(\partial f)/(\partial u)(\partial u)/(\partial x)=t^n(\partial f)/(\partial x)


\implies(\partial f)/(\partial u)t=t^n(\partial f)/(\partial x)

Again, differentiate (1) with respect to t we get,


(\partial)/(\partial t)f(u,v)=nt^(n-1)f(x,y)


\implies (\partial f)/(\partial u)(\partial u)/(\partial t)+(\partial f)/(\partial v)(\partial v)/(\partial t)=nt^(n-1)f(x,y)


\implies x(\partial f)/(\partial u)+y(\partial f)/(\partial v)=nt^(n-1)f(x,y)


\implies xt^(n-1)(\partial f)/(\partial x)+yt^(n-1)(\partial f)/(\partial y)=nt^(n-1)f(x, y) (By putting values of
(\partial f)/(\partial u),(\partial f)/(\partial v))


\therefore x(\partial f)/(\partial x)+y(\partial f)/(\partial y)=nf(x,y)

Hence proved.

User Josephus
by
5.1k points